On the Legitimacy of Political Communities - Koller, Peter; Justus Liebig University Giessen (My University, 2009)
The paper consists of two parts. The first part deals with the normative legitimacy of political communities, such as states and confederations, in general, i.e. their acceptability in light of reasonable standards of efficiency, common good, and justice from the viewpoints of their members on the one hand (internal legitimacy) and their social surroundings on the other (external legitimacy). The requirements of both aspects of legitimacy are specified in a twofold way: as normative ideals and as minimum standards. As to the latter, a political community’s legitimacy minimally requires that it effectively guarantees the fundamental human rights of its members and complies with certain basic precepts of a peaceful and generally beneficial international order. On this basis, the second part scrutinizes the legitimacy of the European Union with regard to its internal and external aspects. This attempt leads to a mixed result. Even though the EU can certainly be regarded, by and large, as a desirable project, it also suffers from a number of considerable defects that weaken its legitimacy.
Keywords: ddc:100; ddc:330